The effects of leverage on investments in maintenance: Evidence from apartments - Lee Seltzer (Federal Reserve Bank of New York, 2021)
This paper studies the sensitivity of investment in apartment building maintenance to building debt levels. I use a novel data set combining housing code violations from forty-five U.S. cities with apartment financing information to show that highly leveraged buildings tend to be less well maintained. I then exploit a natural experiment that effectively increases building leverage for some New York City rentstabilized buildings, but not others. Following the shock, violations increase for affected buildings relative to unaffected buildings. This change in violations is concentrated among more highly leveraged buildings. The results are consistent with debt-reducing investments in maintenance, with consequences for renter quality of life.
Keywords: G3; G31; R30; 330; corporate finance; commercial real estate; housing code violations